2000
DOI: 10.1294/jes.11.45
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Bacteria in Hokkaido Native Horses as Characterized by Microscopic Enumeration and Competitive Polymerase Chain Reaction Assays.

Abstract: Fecal bacteria in Hokkaido native horses were enumerated by their morphology and Gram staining, and then three major cellulolytic species were quantitated by recently developed competitive polymerase chain reaction (cPCR) assays. Fecal bacterial flora in horses showed drastic change between grazing on summer grassland pasture and grazing on winter woodland pasture mainly consisting of bamboo grass (Sasa nipponica). The number of total bacteria was decreased in winter samples, accompanied with a higher proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 12 publications
3
25
0
3
Order By: Relevance
“…Although there is no detailed comparative study, we assumed that fecal microbiota could reflect hindgut microbiota to some extent, since no significant difference in microscopic enumeration was observed between the rectum and colon of horses (Koike et al 2000). This was also reported by Kern et al (1974) who investigated microbes of the terminal colon (close to the rectum) and cecum of the pony.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Although there is no detailed comparative study, we assumed that fecal microbiota could reflect hindgut microbiota to some extent, since no significant difference in microscopic enumeration was observed between the rectum and colon of horses (Koike et al 2000). This was also reported by Kern et al (1974) who investigated microbes of the terminal colon (close to the rectum) and cecum of the pony.…”
Section: Introductionmentioning
confidence: 63%
“…However, there was a clear shift in the proportion of Gram-negative rods, showing significant increases in the winter seasons (Table 1). Koike et al (2000) found that Hokkaido native horses have a bacterial adaptation to low-quality roughage diets on winter woodland pasture in their increased levels of Fibrobacter succinogenes, one of the most potent fibrolytic species present in the equine hindgut. They also observed an increase in Gram-negative rods in winter (Koike et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbial ecology of foregut fermenters is researched extensively (Sylvester et al 2004;Denman & McSweeney 2006;Mosoni et al 2007;Wanapat & Cherdthong 2009). However, the literature regarding microbial ecology of hindgut fermenters is limited to horses (Koike et al 2000;Daly et al 2001;Yamano et al 2008). Results of present study serve as a baseline data for future research in this direction.…”
Section: Gut Microbial Profilementioning
confidence: 99%
“…As amilolíticas, principalmente Lacobacillus e Streptococcus digerem principalmente carboidratos que escapam à digestão enzimática no intestino delgado. Koike et al (2000) encontraram no ceco de cavalos bactérias celulolíticas principalmente de cepas específicas de A Odontoplastia é baseada inicialmente na retomada do equilíbrio da oclusão, através do desgaste da coroa dentária dos molares e incisivos, o tratamento consiste em estabelecer uma mordida coerente sem sobrecarregar a articulação temporomandibular, todos os procedimentos nesta área visam aumentar o conforto do cavalo. O primeiro passo para este tipo de intervenção é a realização de um exame físico do animal e anamnese detalhada para garantir que não existem outras afecções envolvidas.…”
Section: Digestão Dos Carboidratosunclassified